Reduction of WO₃ to WC nanoparticles by reflux reaction₃ - Kumar, R.; Kumar, A.; Singh, S.; Pandey, O.P. (Фізико-хімічна механіка матеріалів, 2013)
WC is an important material mostly used for cutting tool application. Reduction of WO₃ to WC is being done by several techniques. The existing chemical processes involved in its reduction are long and energy consuming. In this work efforts have been made to reduce WO₃ to WC by reflux reaction technique. The composite obtained after reflux reaction has been analyzed to see the feasibility of the conversion of WO₃ to WC. The preliminary study exhibited the feasibility of conversion of WO₃ to WC. The technique seems to be promising one and cost effective for low temperature synthesis of ultrafine WC particles. The synthesized powders were characterized using X-ray diffraction, scanning electron microscope, energy dispersive X-rays, and transmission electron microscopy for phase identification and micro structural analysis. Металокерамічні ванадієві (WC) матеріали використовують для виготовлення різальних інструментів. Перетворюють WO₃ в WC за допомогою різних методик. Хімічні процеси, задіяні у такій редукції, досить тривалі та енергоємні. Проаналізовано композити, отримані після реакції зворотного струму з метою виявлення можливості перетворення WO₃ у WC. Ця методика перспективна і економна для низькотемпературного синтезу ультрадрібних частинок WC. Синтезовані порошки досліджено методами рентгенівського дифракційного аналізу, сканівної електронної мікроскопії, та енергорозсіювального рентгенівського аналізу, трансемісійної електронної мікроскопії. Металлокерамические ванадиевые (WC) материалы используют для изготовления режущих инструментов. Превращение WO₃ в WC проводят с помощью разных методик. Химические процессы, которые принимают участие в такой редукции, достаточно продолжительные и энергоемкие. Проанализированы композиты, полученные после реакции обратного тока с целью выявления возможности превращения WO₃ в WC. Данная методика является перспективной и экономной для низкотемпературного синтеза ультрамелких частиц WC. Синтезированные порошки исследовали методами рентгеновского дифракционного анализа, сканирующей электронной микроскопии, энергорассеивающего рентгеновского анализа, трансэмиссионной электронной микроскопии.